2017
DOI: 10.1186/s12878-017-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Case report: primary osteonecrosis associated with thrombophilia-hypofibrinolysis and worsened by testosterone therapy

Abstract: BackgroundFamilial and acquired thrombophilia are often etiologic for idiopathic hip and jaw osteonecrosis (ON), and testosterone therapy (TT) can interact with thrombophilia, worsening ON.Case presentationCase 1: A 62-year-old Caucasian male (previous deep venous thrombosis), on warfarin 1 year for atrial fibrillation (AF), had non-specific right hip-abdominal pain for 2 years. CT scan revealed bilateral femoral head ON without collapse. Coagulation studies revealed Factor V Leiden (FVL) heterozygosity, 4G/4G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…None of the 16 patients had osteonecrosis before starting TT. Idiopathic osteonecrosis, with intra-osseous venous thrombosis, is often caused by thrombophilia [21,27,49], often develops after starting TT, and its progression may be slowed or stopped by discontinuation of TT, and, thereafter, anticoagulation [18,50,51,52,53]. Of the 16 cases, 5 (31%) were FVL heterozygotes versus 4 of 48 patients who had osteonecrosis and were not receiving TT ( p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the 16 patients had osteonecrosis before starting TT. Idiopathic osteonecrosis, with intra-osseous venous thrombosis, is often caused by thrombophilia [21,27,49], often develops after starting TT, and its progression may be slowed or stopped by discontinuation of TT, and, thereafter, anticoagulation [18,50,51,52,53]. Of the 16 cases, 5 (31%) were FVL heterozygotes versus 4 of 48 patients who had osteonecrosis and were not receiving TT ( p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 cases, 5 (31%) were FVL heterozygotes versus 4 of 48 patients who had osteonecrosis and were not receiving TT ( p = 0.04). Subsequently, we reported 2 additional cases [50] of osteonecrosis after starting TT, both found to be heterozygous for the FVL mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Possible etiologic factors for exposed bone lesions were reported in the literature and consist of trauma, odontogenic infections, herpes zoster infection associated osteonecrosis, HIV-associated necrotizing ulcerative periodontitis, benign sequestration of the lingual plate [1], long-term corticosteroid usage [4], ischaemia, occlusion, and coagulopathies [5,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of direct oral anticoagulants was highlighted in other case reports, as well. One patient with important thrombophilic burden and history of deep venous thrombosis (anticoagulated with warfarin for atrial fibrillation and symptomatic for ONFH) showed complete resolution of symptoms after 8 months on apixaban 5 mg bid [111]. Milgrom et al [110] reported the case of a woman diagnosed at the age of 26 with primary multifocal ON, in context of complex thrombophilia (FV Leiden heterozygosity, C677T MTHFR homozygosity, and hypofibrinolytic 4G4G homozygosity for the PAI-1 gene).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%